Metabolomic and Proteomic Profiles Reveal the Dynamics of Primary Metabolism during Seed Development of Lotus (Nelumbo nucifera) - Wang, Lei; Fu, Jinlei; Li, Ming; Fragner, Lena; Weckwerth, Wolfram; Yang, Pingfang (Frontiers in Plant Science, 2016)
Sacred lotus (Nelumbo nucifera) belongs to Nelumbonaceae family. Its seeds are widely consumed in Asia countries as snacks or even medicine. Besides the market values, lotus seed also plays crucial roles in lotus life cycle. Consequently, it is essential to gain a comprehensive understanding of the development of lotus seed. During its development, lotus seed undergoes cell division, expansion, reserve accumulation, desiccation and maturation phases. We observed morphological and biochemical changes from 10 to 25 days after pollination (DAP) which was corresponding to the reserve synthesis and accumulation phase. The volume of the seed expanded until 20 DAP with the color of the seed coat changing from yellow-green to dark green and gradually fading again. Starch and protein rapidly accumulated from 15 to 20 DAP. To further reveal the metabolism adaptation, primary metabolites and proteins profiles were obtained using mass spectrometry based platforms. Metabolites and enzymes involved in sugar metabolism, glycolysis, TCA cycle and amino acids metabolism showed sequential dynamics enabling the clear separation of the different metabolic states during lotus seed development. The integration of the data revealed a highly significant metabolic switch at 15 DAP going through a transition of metabolically highly active tissue to the preparation of storage tissue. The results provide reference data set for the evaluation of primary metabolism during lotus seed development.